Kaleckian Models of Growth in a Stock-Flow Monetary Framework: A Neo-Kaldorian Model - Marc Lavoie; Wynne Godley (Levy Economics Institute of Bard College, 2000)
This paper presents a simple growth model grounded in a stock-flow monetary accounting framework. The framework ensures that all stocks and all flows are accounted for and that the real and financial sides of the economy are coherent with one another. Credit, money, equities and stocks of real capital link periods of time with one another in articulated sequences. Wealth is allocated between assets on Tobinesque principles but no equilibrium condition is necessary to bring the "demand" for money into equivalence with its "supply". Growth and profit rates, as well as valuation, debt and capacity utilization ratios are analysed using simulations in which a growing economy is assumed to be shocked by changes in interest rates, liquidity preference, real wages, and the parameters which determine how firms finance investment. acceleration in recent years that might explain the growth in earnings inequality. There has also been no dramatic change in the number of workers who are undereducated. These results reinforce the conclusions of earlier work that reports of a growing skills mismatch are likely overdrawn.
Keywords: 330